Positive electrode material, preparation method, application, positive electrode plate, zinc ion battery and vehicle

By doping manganese elements into Zn3V3O8 nanodisk material, more stable vanadium ions are formed and electron transfer is promoted during Zn2+ embedding/deintercalation process, the problems of low specific capacity and poor cycle stability of zinc positive electrode materials are solved, and the better electrochemical performance of zinc ion batteries is achieved.

CN119852397APending Publication Date: 2025-04-18DEEPAL AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510086569.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing zinc cathode materials have problems such as low specific capacity and poor cycle stability.

Method used

Manganese-doped Zn3V3O8 nanodisk material is used as the positive electrode material to form more stable vanadium ions through electrochemical transformation, improving the cyclic stability of the material, and promoting electron transfer in the Zn2+ embedding/deintercalation process through Mn2+ doping, thereby increasing the specific capacity.

Benefits of technology

It effectively improves the cyclic stability and specific capacity of zinc ion batteries, improves the electrochemical performance, and makes zinc ion batteries perform better in terms of discharge specific capacity, rate performance and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852397A_ABST
    Figure CN119852397A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode material, a preparation method, application, a positive electrode plate, a zinc ion battery and a vehicle. And the positive electrode material comprises a Zn3V3O8 nanodisk material doped with manganese. The invention also provides a preparation method of the positive electrode material, which comprises the following steps: mixing a metavanadate solution, a zinc salt solution and a manganese salt solution to obtain a mixed solution; and carrying out solvothermal reaction on the mixed solution, and calcining to obtain the manganese-doped Zn3V3O8 nanodisk material. The invention also provides a positive pole piece taking the positive pole material as a positive pole active material and application of the positive pole material as an electrode active material of a battery. The invention also provides a positive pole piece taking the positive pole material as a positive pole active material. The invention also provides a zinc ion battery taking the positive pole piece as a positive pole. The invention also provides a vehicle which is provided with the zinc ion battery provided by the invention. According to the invention, the problems of low specific capacity and poor cycling stability of the existing zinc positive electrode material are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a positive electrode material, a preparation method, an application, a positive electrode sheet, a zinc ion battery and a vehicle. Background Art

[0002] In view of the energy crisis, environmental pollution and the continuous consumption of renewable resources, the society's demand for the development of clean and efficient new energy storage devices is growing rapidly. Compared with lithium-ion batteries, which are expensive and have safety risks, aqueous zinc-ion batteries have attracted much attention for their moderate energy density, excellent safety, low cost and simple assembly process. In addition, the zinc negative electrode has a high theoretical specific capacity (820mAhg -1 ) and a lower redox potential (0.76 V vs. standard hydrogen electrode), in the electrochemical reaction, Zn 2+ The double electron transfer process of Zn / Zn is different from that of monovalent alkali metal ions (such as Li + , K + 、Na + Zinc-ion batteries are considered to be one of the new energy storage technologies that are expected to replace lithium-ion batteries in the future. Vanadium oxides have attracted wide attention as positive electrode materials for zinc-ion batteries due to their diverse valence states, high theoretical specific capacity, and good electrochemical activity. When zinc-ion batteries undergo electrochemical reactions, Zn 2+ It has a strong electrostatic attraction to vanadium oxide, and the VO polyhedron is easy to deform. Usually, vanadium oxide will have a structural collapse problem after a period of charge and discharge process, which greatly reduces the long cycle stability of the battery. Studies have shown that by introducing new substances into vanadium oxide, the problem of structural collapse of vanadium oxide can be alleviated to a certain extent. For example, a Zn3V3O8 / VO2 composite material is disclosed in the prior art, and its preparation method is: based on the solid-phase ion pre-insertion method, zinc acetate dihydrate and vanadium dioxide are mixed, and calcined under a protective atmosphere to synthesize a heterostructured Zn3V3O8 / VO2 composite material. The Zn3V3O8 / VO2 heterostructure material with rich phase boundaries is used as the positive electrode material of the zinc ion battery. The heterogeneous interface in the Zn3V3O8 / VO2 heterostructure can provide more locations for the storage of zinc ions, thereby effectively increasing the capacity of the electrode. At the same time, the heterostructure improves the structural stability to a certain extent. Summary of the invention

[0003] In view of the deficiencies in the prior art, the object of the present invention is to provide a positive electrode material, a preparation method, an application, a positive electrode plate, a zinc ion battery and a vehicle, so as to simultaneously solve the problems of low specific capacity and poor cycle stability of existing zinc positive electrode materials.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A positive electrode material includes a Zn3V3O8 nanodisk material doped with manganese.

[0005] According to the above technical means, Zn3V3O8 will undergo electrochemical transformation during the first charge and discharge process, thereby inducing a phase change in the material, from Zn3V3O8 to high-valent vanadate Zn3V2O7(OH)22H2O and Zn x V2O 5-y n H2O makes the positive electrode material form more stable vanadium ions, effectively improving the cycle stability of the positive electrode material, thereby making a battery, which can improve the cycle stability of the battery. At the same time, by doping manganese elements in the Zn3V3O8 nanodisk material, the Mn with high electrochemical activity and high conductivity 2+ Replaced part of Zn 2+ , which can effectively promote Zn 2+ Rapid electron transfer during the embedding / de-embedding process effectively improves the specific capacity of the material. At the same time, it solves the problems of low specific capacity and poor cycle stability of existing zinc positive electrode materials. This allows zinc ion batteries using this positive electrode material to achieve more excellent electrochemical performance.

[0006] Among them, Zn3V3O8 is composed of a three-dimensional framework composed of multiple V(Zn2)O6 octahedra. Zn3V3O8 undergoes electrochemical transformation during the first charge and discharge process, thereby inducing a phase change in the material, from Zn3V3O8 to high-valent vanadate Zn3V2O7(OH)22H2O and Zn x V2O 5-y n H2O. Since the vanadium ions in the material have a higher and more stable valence (+5), the positive electrode material also has better structural stability; at the same time, the introduction of highly active elements for substitution and doping effectively improves the specific capacity of the material. The zinc storage mechanism of the Zn3V3O8 positive electrode is Zn 2+ With H + Co-embedded.

[0007] The first charge and discharge process of the Zn3V3O8 positive electrode can be described by the following formula: First time charging: a Zn3V3O8+ m H2O↔Zn b V2O7(OH)22H2O+Zn c V2O 5-x n H2O+H + +e − First discharge: Zn bV2O7(OH)22H2O+Zn c V2O 5-x n H2O+ f H + + g Zn 2+ + l e − ↔ h H J Zn k V3O8+Zn p V 2-q O7(OH)22H2O.

[0008] Among them, x, y, n, m, a, b, c, h, j, k, l, p, and q are positive numbers.

[0009] Preferably, the Zn3V3O8 nano-disk material is doped with Mn 2+ .

[0010] Preferably, the Zn3V3O8 nanodisk material is a spinel-type Zn3V3O8 nanodisk material.

[0011] The spinel structure of Zn3V3O8 nanodisk material has stable ion diffusion channels, zinc-rich properties and a two-electron reaction mechanism during charge and discharge (V 5+ ↔V 3+ ), which makes the spinel-structured Zn3V3O8 nanodisk material have excellent zinc storage performance.

[0012] Preferably, the doping amount of manganese is 0-10%.

[0013] The present invention also provides a method for preparing the positive electrode material according to the present invention, comprising the following steps: S1, mixing a metavanadate solution, a zinc salt solution and a manganese salt solution to obtain a mixed solution; S2, subjecting the mixed solution to a solvothermal reaction to obtain a precursor product; S3. calcining the precursor product to obtain a Zn3V3O8 nanodisk material doped with manganese.

[0014] By mixing a metavanadate solution, a zinc salt solution and a manganese salt solution, followed by a solvothermal reaction and calcination, a Zn3V3O8 nanodisk material doped with manganese can be effectively prepared. A solvothermal reaction is a chemical reaction carried out in a closed container that can be carried out at a relatively low temperature, which helps to improve the synthesis efficiency of the material and the purity of the product. This method can obtain a nanodisk material with a specific morphology, and this structure may have excellent electrochemical properties, such as a high specific surface area and good ion conductivity. High-temperature calcination can further improve the crystallinity of the product, which helps to improve the electrochemical performance. Doping manganese elements in Zn3V3O8 materials can improve the electrochemical properties of the material, such as improving its conductivity and cycle stability, thereby possibly improving the performance of the battery. By adjusting the conditions of the solvothermal reaction and calcination, such as temperature, time, atmosphere, etc., the morphology and performance of the final product can be effectively controlled to meet different application requirements.

[0015] Preferably, in S2, the temperature of the solvent thermal reaction is 180°C to 200°C.

[0016] Preferably, in S2, the temperature of the solvothermal reaction is 180°C.

[0017] Preferably, in S2, the solvent thermal reaction time is 21 to 24 hours.

[0018] Preferably, in S2, the solvent thermal reaction time is 24 hours.

[0019] Preferably, in S3, the calcination temperature is 580°C to 620°C.

[0020] Preferably, in S3, the calcination temperature is 600°C.

[0021] Preferably, in S3, the calcination time is 5 to 7 hours.

[0022] Preferably, in S3, the calcination time is 6 hours.

[0023] Preferably, in S3, calcination is carried out in an inert atmosphere, and the temperature increase method of calcination is programmed temperature increase, and the rate of the programmed temperature increase is 8-12° C. / min.

[0024] Preferably, the rate of the programmed temperature increase is 10°C / min.

[0025] Preferably, the metavanadate is selected from one or both of sodium metavanadate and sodium metavanadate dihydrate.

[0026] Preferably, the zinc salt is selected from one or both of zinc acetate and zinc acetate dihydrate.

[0027] Preferably, the manganese salt is selected from one or both of manganese acetate and manganese acetate tetrahydrate.

[0028] Preferably, the metavanadate solution is obtained by dissolving metavanadate in an organic solvent.

[0029] Preferably, the zinc salt solution is obtained by dissolving a zinc salt in water.

[0030] Preferably, the manganese salt solution is obtained by dissolving a manganese salt in water.

[0031] Preferably, the organic solvent is selected from ethylene glycol.

[0032] Preferably, S1 comprises: adding sodium metavanadate dihydrate (NaVO3·2H2O) to ethylene glycol, stirring electromagnetically at room temperature for 5 hours until completely dissolved, to obtain a sodium metavanadate solution; adding zinc acetate dihydrate and manganese acetate tetrahydrate to deionized water, stirring electromagnetically at room temperature for 5 minutes until completely dissolved, to obtain a mixed solution of zinc acetate and manganese acetate; adding the mixed solution of zinc acetate and manganese acetate dropwise to the sodium metavanadate solution, stirring fully for 2 hours, to obtain a milky yellow mixed solution.

[0033] Preferably, S2 comprises: transferring the milky yellow mixed solution into a polytetrafluoroethylene reactor, performing a solvent thermal reaction at a temperature of 180°C for 24 hours, and naturally cooling to room temperature after the reaction is completed to obtain a black product; after filtering the black product, washing it three times with deionized water and anhydrous ethanol respectively, and vacuum drying it at a temperature of 70°C for 10 hours to obtain a precursor product.

[0034] Preferably, S3 includes: transferring the black powder precursor product into a tubular furnace, heating it to 600 °C at a rate of 10 °C / min under an inert gas argon (Ar) atmosphere, and then calcining it at 600 °C for 6 h. After the reaction is completed, it is naturally cooled to room temperature to obtain a Zn3V3O8 nanodisk material doped with manganese.

[0035] The present invention also provides an application of the positive electrode material prepared by the preparation method of the present invention as an electrode active material of a battery.

[0036] The present invention also provides a positive electrode plate, wherein the positive electrode active material in the positive electrode plate is selected from the positive electrode material prepared by the preparation method of the present invention.

[0037] The present invention also provides a zinc ion battery, which uses the positive electrode sheet as described in the present invention as the positive electrode of the zinc ion battery.

[0038] The present invention also provides a vehicle, on which the zinc ion battery according to the present invention is installed.

[0039] Beneficial effects of the present invention: The positive electrode material of the present invention is that Zn3V3O8 undergoes electrochemical conversion during the first charge and discharge process, thereby inducing a phase change in the material, and is converted from Zn3V3O8 into high-valent vanadate Zn3V2O7(OH)22H2O and Zn x V2O 5-y n H2O makes the positive electrode material form more stable vanadium ions, effectively improving the overall stability of the positive electrode material, so as to make a battery, which can improve the cycle stability of the battery. At the same time, by doping manganese elements in the Zn3V3O8 nanodisk material, the Mn with high electrochemical activity and high conductivity 2+ Can effectively promote Zn 2+ The rapid electron transfer during the embedding / de-embedding process effectively improves the material's specific capacity, allowing zinc-ion batteries using this positive electrode material to simultaneously achieve more excellent electrochemical performance.

[0040] The preparation method of the positive electrode material of the present invention can effectively prepare a Zn3V3O8 nanodisk material doped with manganese by mixing a metavanadate solution, a zinc salt solution and a manganese salt solution, and then performing a solvent thermal reaction and calcination. The solvent thermal reaction ensures the two-dimensional nano morphology of the product, and the subsequent calcination makes the product have good crystallinity, so that the prepared positive electrode material has good electrochemical performance.

[0041] The zinc ion battery of the present invention adopts the positive electrode plate of the present invention as the positive electrode of the zinc ion battery, which can effectively improve the discharge specific capacity, rate performance and cycle stability of the battery at the same time, and has promotion and application value in the technical field of zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is the XRD pattern of Zn3V3O8 nanodisk material; Figure 2 This is the SEM image of the Zn3V3O8 nanodisk material; Figure 3 TEM image of Zn3V3O8 nanodisk material; Figure 4 The cyclic voltammetry curve and constant current charge-discharge curve of the zinc ion button battery; Figure 5 This is the rate performance result diagram of zinc ion button battery; Figure 6 This is a graph showing the cycling performance results of a zinc ion button battery. DETAILED DESCRIPTION

[0043] The following will describe the embodiments of the present invention with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.

[0044] It should be noted that the illustrations provided in the following embodiments are only schematic illustrations of the basic concept of the present invention, and thus the drawings only show components related to the present invention rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.

[0045] In the following description, numerous details are discussed to provide a more thorough explanation of the embodiments of the present application. However, it is obvious to those skilled in the art that the embodiments of the present application can be implemented without these specific details.

[0046] The present invention intends to disclose a positive electrode material, a preparation method, an application, a positive electrode plate, a zinc ion battery and a vehicle, so as to solve the problems of poor cycle stability and low specific capacity of existing zinc positive electrode materials.

[0047] Among them, a positive electrode material includes Zn3V3O8 nanodisk material doped with manganese.

[0048] During the first charge and discharge process, Zn3V3O8 will undergo electrochemical transformation, inducing a phase change in the material, from Zn3V3O8 to high-valent vanadate Zn3V2O7(OH)22H2O and Zn x V2O 5-y n H2O makes the positive electrode material form more stable vanadium ions, effectively improving the overall stability of the positive electrode material, so as to make a battery, which can improve the cycle stability of the battery. At the same time, by doping manganese elements in the Zn3V3O8 nanodisk material, the Mn with high electrochemical activity and high conductivity 2+ Can effectively promote Zn 2+ Rapid electron transfer during the embedding / de-embedding process effectively improves the specific capacity of the material. At the same time, it solves the problems of low specific capacity and poor cycle stability of existing zinc positive electrode materials. The zinc ion battery using this positive electrode material can simultaneously obtain more excellent electrochemical performance.

[0049] In some embodiments, the Zn3V3O8 nanodisk material is doped with Mn 2+ .

[0050] In some embodiments, the Zn3V3O8 nanodisk material is a spinel-type Zn3V3O8 nanodisk material.

[0051] The spinel structure of Zn3V3O8 nanodisk material has stable ion diffusion channels, zinc-rich properties and a two-electron reaction mechanism during charge and discharge (V 5+ ↔V 3+ ), which makes the spinel-structured Zn3V3O8 nanodisk material have excellent zinc storage performance.

[0052] In some embodiments, the doping amount of manganese is 0-10%.

[0053] In some embodiments, a method for preparing a positive electrode material is also provided, comprising the following steps: S1, mixing a metavanadate solution, a zinc salt solution and a manganese salt solution to obtain a mixed solution; S2, subjecting the mixed solution to a solvothermal reaction to obtain a precursor product; S3. calcining the precursor product to obtain a Zn3V3O8 nanodisk material doped with manganese.

[0054] By mixing a metavanadate solution, a zinc salt solution and a manganese salt solution, followed by a solvothermal reaction and calcination, a Zn3V3O8 nanodisk material doped with manganese can be effectively prepared. A solvothermal reaction is a chemical reaction carried out in a closed container that can be carried out at a relatively low temperature, which helps to improve the synthesis efficiency of the material and the purity of the product. This method can obtain a nanodisk material with a specific morphology, and this structure may have excellent electrochemical properties, such as a high specific surface area and good ionic conductivity. Doping manganese elements in Zn3V3O8 materials can improve the electrochemical properties of the material, such as improving its conductivity and cycle stability, thereby potentially improving the performance of the battery. By adjusting the conditions of the solvothermal reaction and calcination, such as temperature, time, atmosphere, etc., the morphology and properties of the final product can be effectively controlled to meet different application requirements.

[0055] In some embodiments, in S2, the temperature of the solvothermal reaction is 180°C to 200°C.

[0056] Exemplarily, in S2, the temperature of the solvothermal reaction is 180°C.

[0057] In some embodiments, in S2, the solvent thermal reaction time is 21 to 24 hours.

[0058] Exemplarily, in S2, the solvent thermal reaction time is 24 hours.

[0059] In some embodiments, in S3, the calcination temperature is 580°C to 620°C.

[0060] Exemplarily, in S3, the calcination temperature is 600°C.

[0061] In some embodiments, in S3, the calcination time is 5 to 7 hours.

[0062] Exemplarily, in S3, the calcination time is 6 hours.

[0063] Exemplarily, in S3, calcination is carried out in an inert atmosphere, and the temperature increase method of calcination is programmed temperature increase, and the rate of the programmed temperature increase is 10° C. / min.

[0064] In some embodiments, the metavanadate is selected from one or both of sodium metavanadate and sodium metavanadate dihydrate.

[0065] In some embodiments, the zinc salt is selected from one or both of zinc acetate and zinc acetate dihydrate.

[0066] In some embodiments, the manganese salt is selected from one or both of manganese acetate and manganese acetate tetrahydrate.

[0067] In some embodiments, the metavanadate solution is obtained by dissolving metavanadate in an organic solvent.

[0068] In some embodiments, the zinc salt solution is obtained by dissolving a zinc salt in water.

[0069] In some embodiments, the manganese salt solution is obtained by dissolving a manganese salt in water.

[0070] Exemplarily, the organic solvent is selected from ethylene glycol.

[0071] Exemplarily, S1 includes: adding sodium metavanadate dihydrate (NaVO3·2H2O) to ethylene glycol, stirring electromagnetically at room temperature for 5 hours until completely dissolved, to obtain a sodium metavanadate solution; adding zinc acetate dihydrate and manganese acetate tetrahydrate to deionized water, stirring electromagnetically at room temperature for 5 minutes until completely dissolved, to obtain a mixed solution of zinc acetate and manganese acetate; adding the mixed solution of zinc acetate and manganese acetate dropwise to the sodium metavanadate solution, stirring thoroughly for 2 hours, to obtain a milky yellow mixed solution.

[0072] Exemplarily, S2 includes: transferring the milky yellow mixed solution into a polytetrafluoroethylene reactor, performing a solvent thermal reaction at a temperature of 180°C for 24 hours, and naturally cooling to room temperature after the reaction is completed to obtain a black product; after filtering the black product, washing it with deionized water and anhydrous ethanol three times each, and vacuum drying it at a temperature of 70°C for 10 hours to obtain a precursor product.

[0073] Exemplarily, S3 includes: transferring the black powder precursor product into a tubular furnace, heating it to 600 °C at a rate of 10 °C / min under an inert gas argon (Ar) atmosphere, and then calcining it at 600 °C for 6 h. After the reaction is completed, it is naturally cooled to room temperature to obtain a Zn3V3O8 nanodisk material doped with manganese.

[0074] In some embodiments, a use of a positive electrode material as an electrode active material of a battery is also provided.

[0075] In some embodiments, a positive electrode plate is also provided, and the positive electrode active material in the positive electrode plate is selected from the above-mentioned positive electrode materials.

[0076] In some embodiments, a zinc ion battery is also provided, which uses the above-mentioned positive electrode plate as the positive electrode of the zinc ion battery.

[0077] In some embodiments, a vehicle is also provided, on which the above-mentioned zinc ion battery is installed.

[0078] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the preparation method of the positive electrode material and zinc ion battery of the present invention will be further described in detail below in conjunction with specific embodiments and drawings. Obviously, the specific embodiments described are only a part of the embodiments of the present application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its application. Based on the specific embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without paying creative work belong to the scope of protection of the present application.

[0079] If no specific techniques or conditions are specified in the specific embodiments, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0080] Example 1 S1. Add 10 mmol sodium metavanadate dihydrate (NaVO3·2H2O) into 150 mL ethylene glycol and stir under electromagnetic stirring at room temperature for 5 h until it is completely dissolved to obtain a sodium metavanadate solution. 10 mmol of zinc acetate dihydrate and 0.25 mmol of manganese acetate tetrahydrate were added into 100 mL of deionized water, and stirred at room temperature for 5 min until they were completely dissolved to obtain a mixed solution of zinc acetate and manganese acetate; The mixed solution of zinc acetate and manganese acetate was added dropwise to the sodium metavanadate solution and stirred for 2 h to obtain a milky yellow mixed solution.

[0081] S2. Transfer the milky yellow mixed solution into a 100 mL polytetrafluoroethylene reactor and perform solvent thermal reaction at 180°C for 24 h. After the reaction is completed, cool it naturally to room temperature to obtain a black product. After filtering the black product, wash it three times with deionized water and anhydrous ethanol respectively, and vacuum dry it at 70°C for 10 h to obtain a precursor product.

[0082] S3, the black powder precursor product was transferred to a tube furnace, and the temperature was raised to 600 ° C at a rate of 10 ° C / min in an inert gas argon (Ar) atmosphere, and then kept at 600 ° C for calcination for 6 h. After the reaction was completed, it was naturally cooled to room temperature to obtain a 2.5% Mn doped 2+ The Zn3V3O8 nanodisk material is named 2.5-ZnVO.

[0083] Example 2 A method for preparing a positive electrode material comprises the following steps: S1. Add 10 mmol sodium metavanadate dihydrate (NaVO3·2H2O) into 150 mL ethylene glycol and stir under electromagnetic stirring at room temperature for 5 h until it is completely dissolved to obtain a sodium metavanadate solution. 10 mmol of zinc acetate dihydrate and 0.5 mmol of manganese acetate tetrahydrate were added into 100 mL of deionized water, and stirred at room temperature for 5 min until completely dissolved to obtain a mixed solution of zinc acetate and manganese acetate; The mixed solution of zinc acetate and manganese acetate was added dropwise to the sodium metavanadate solution and stirred for 2 h to obtain a milky yellow mixed solution.

[0084] S2. Transfer the milky yellow mixed solution into a 100 mL polytetrafluoroethylene reactor and perform solvent thermal reaction at 180°C for 24 h. After the reaction is completed, cool it naturally to room temperature to obtain a black product. After filtering the black product, wash it three times with deionized water and anhydrous ethanol respectively, and vacuum dry it at 70°C for 10 h to obtain a precursor product.

[0085] S3, the black powder precursor product was transferred to a tube furnace, and the temperature was raised to 600 ° C at a rate of 10 ° C / min in an inert gas argon (Ar) atmosphere, and then kept at 600 ° C for calcination for 6 h. After the reaction was completed, it was naturally cooled to room temperature to obtain a 5% Mn doped 2+ The Zn3V3O8 nanodisk material is named 5-ZnVO.

[0086] Example 3 A method for preparing a positive electrode material comprises the following steps: S1. Add 10 mmol sodium metavanadate dihydrate (NaVO3·2H2O) into 150 mL ethylene glycol and stir under electromagnetic stirring at room temperature for 5 h until it is completely dissolved to obtain a sodium metavanadate solution. 10 mmol of zinc acetate dihydrate and 1 mmol of manganese acetate tetrahydrate were added into 100 mL of deionized water, and stirred at room temperature for 5 min until completely dissolved to obtain a mixed solution of zinc acetate and manganese acetate; The mixed solution of zinc acetate and manganese acetate was added dropwise to the sodium metavanadate solution and stirred for 2 h to obtain a milky yellow mixed solution.

[0087] S2. Transfer the milky yellow mixed solution into a 100 mL polytetrafluoroethylene reactor and perform solvent thermal reaction at 180°C for 24 h. After the reaction is completed, cool it naturally to room temperature to obtain a black product. After filtering the black product, wash it three times with deionized water and anhydrous ethanol respectively, and vacuum dry it at 70°C for 10 h to obtain a precursor product.

[0088] S3, the black powder precursor product was transferred to a tube furnace, and the temperature was raised to 600 ° C at a rate of 10 ° C / min in an inert gas argon (Ar) atmosphere, and then kept at 600 ° C for calcination for 6 h. After the reaction was completed, it was naturally cooled to room temperature to obtain a 10% Mn doped 2+ The Zn3V3O8 nanodisk material is named 10-ZnVO.

[0089] Example 4 A method for preparing a zinc ion battery comprises the following steps: Preparation of positive electrode: The positive electrode prepared in Example 1 is doped with 2.5% Mn 2+ The Zn3V3O8 nanodisk material is used as the positive electrode active material; A certain volume of N-methylpyrrolidone solution (NMP) was added to an agate mortar. Then, the positive electrode active material, conductive agent (acetylene black) and binder (polyvinylidene fluoride) were added to the above solution in a mass ratio of 7:2:1, and mixed and ground evenly until there was no particle feeling. The obtained mixed slurry was evenly coated on the titanium foil, and the coating area was about 1 cm -2 The titanium foil was placed in a vacuum drying oven at 60°C and dried for 12 hours. After drying, it was weighed and the loading mass of the positive electrode active material on the titanium foil was about 1.5~2.0 mg cm- 2 .

[0090] Assembly of zinc ion battery: The positive electrode sheet prepared above was used as the positive electrode, zinc foil was used as the negative electrode, and 3 M (mol L -1)Zn(CF3SO3)2 aqueous solution is used as electrolyte, glass fiber filter paper is used as diaphragm, and assembled in air to obtain an aqueous zinc ion battery.

[0091] Example 5 A method for preparing a zinc ion battery comprises the following steps: Preparation of positive electrode: The positive electrode prepared in Example 2 is doped with 5% Mn 2+ The Zn3V3O8 nanodisk material is used as the positive electrode active material; A certain volume of N-methylpyrrolidone solution (NMP) was added to an agate mortar. Then, the positive electrode active material, conductive agent (acetylene black) and binder (polyvinylidene fluoride) were added to the above solution in a mass ratio of 7:2:1, and mixed and ground evenly until there was no particle feeling. The obtained mixed slurry was evenly coated on the titanium foil, and the coating area was about 1 cm -2 The titanium foil was placed in a vacuum drying oven at 60°C and dried for 12 hours. After drying, it was weighed and the loading mass of the positive electrode active material on the titanium foil was about 1.5~2.0 mg cm- 2 .

[0092] Assembly of zinc ion battery: The positive electrode sheet prepared above was used as the positive electrode, zinc foil was used as the negative electrode, and 3 M (mol L -1 )Zn(CF3SO3)2 aqueous solution is used as electrolyte, glass fiber filter paper is used as diaphragm, and assembled in air to obtain an aqueous zinc ion battery.

[0093] Example 6 A method for preparing a zinc ion battery comprises the following steps: Preparation of positive electrode: The positive electrode prepared in Example 3 is doped with 10% Mn 2+ The Zn3V3O8 nanodisk material is used as the positive electrode active material; A certain volume of N-methylpyrrolidone solution (NMP) was added to an agate mortar. Then, the positive electrode active material, conductive agent (acetylene black) and binder (polyvinylidene fluoride) were added to the above solution in a mass ratio of 7:2:1, and mixed and ground evenly until there was no particle feeling. The obtained mixed slurry was evenly coated on the titanium foil, and the coating area was about 1 cm -2 The titanium foil was placed in a vacuum drying oven at 60°C and dried for 12 hours. After drying, it was weighed and the loading mass of the positive electrode active material on the titanium foil was about 1.5~2.0 mg cm- 2 .

[0094] Assembly of zinc ion battery: The positive electrode sheet prepared above was used as the positive electrode, zinc foil was used as the negative electrode, and 3 M (mol L -1)Zn(CF3SO3)2 aqueous solution is used as electrolyte, glass fiber filter paper is used as diaphragm, and assembled in air to obtain an aqueous zinc ion battery.

[0095] Comparative Example 1 A method for preparing a positive electrode material comprises the following steps: S1. Add 10 mmol sodium metavanadate dihydrate (NaVO3·2H2O) into 150 mL ethylene glycol and stir under electromagnetic stirring at room temperature for 5 h until it is completely dissolved to obtain a sodium metavanadate solution. Add 10 mmol zinc acetate dihydrate into 100 mL deionized water and stir at room temperature for 5 min until it is completely dissolved to obtain a zinc acetate solution; The zinc acetate solution was added dropwise to the sodium metavanadate solution and stirred thoroughly for 2 h to obtain a mixed solution.

[0096] S2. The mixed solution was transferred into a 100 mL polytetrafluoroethylene reactor, and the solvent thermal reaction was carried out at a temperature of 180°C for 24 h. After the reaction was completed, it was naturally cooled to room temperature to obtain an intermediate product. After the intermediate product was filtered, it was washed three times with deionized water and anhydrous ethanol respectively, and vacuum dried at a temperature of 70°C for 10 h to obtain a precursor product.

[0097] S3. The precursor product was transferred into a tube furnace. Under an inert gas argon (Ar) atmosphere, the temperature was raised to 600 °C at a rate of 10 °C / min. Then, the temperature was kept constant at 600 °C for calcination for 6 h. After the reaction was completed, it was naturally cooled to room temperature to obtain a Zn3V3O8 nanodisk material, named ZnVO.

[0098] Detection and analysis 1) X-ray diffraction analysis The 2.5% Mn-doped 2+ The Zn3V3O8 nanodisk material prepared in Example 2 is doped with 5% Mn 2+ The Zn3V3O8 nanodisk material prepared in Example 3 is doped with 10% Mn 2+ The Zn3V3O8 nanodisk material and the undoped Zn3V3O8 nanodisk material prepared in Example 1 were subjected to X-ray diffraction analysis. The results are as follows: Figure 1 shown.

[0099] Figure 1 In the embodiment, ZnVO corresponds to the undoped Zn3V3O8 nanodisk material prepared in the comparative example 1; 2.5-ZnVO corresponds to the nanodisk material doped with 2.5% Mn prepared in the embodiment 1. 2+ Zn3V3O8 nanodisk material; 5-ZnVO corresponds to the 5% Mn doped Zn3V3O8 nanodisk material prepared in Example 2.2+ Zn3V3O8 nanodisk material; 10-ZnVO corresponds to the Zn3V3O8 nanodisk material doped with 10% Mn prepared in Example 3 2+ Zn3V3O8 nanodisk materials.

[0100] from Figure 1 The analysis shows that the doped 2.5% Mn 2+ The Zn3V3O8 nanodisk material prepared in Example 2 is doped with 5% Mn 2+ The Zn3V3O8 nanodisk material prepared in Example 3 is doped with 10% Mn 2+ The diffraction peak positions of the Zn3V3O8 nanodisk material and the undoped Zn3V3O8 nanodisk material prepared in Example 1 are consistent with the spinel Zn3V3O8 standard card, proving that the spinel Zn3V3O8 materials were successfully prepared in Example 1, Example 2, Example 3 and Control Example 1.

[0101] 2) Scanning electron microscopy analysis The 2.5% Mn-doped 2+ The Zn3V3O8 nanodisk material prepared in Example 2 is doped with 5Mn 2+ The Zn3V3O8 nano-disk material prepared in Example 3 is doped with 10% Mn 2+ The undoped Zn3V3O8 nanodisk material prepared in Example 1 was subjected to scanning electron microscopy analysis. The results are as follows: Figure 2 shown.

[0102] in, Figure 2 a corresponds to the undoped Zn3V3O8 nanodisk material prepared in Comparative Example 1; Figure 2 b corresponds to the 2.5% Mn-doped 2+ Zn3V3O8 nanodisk materials; Figure 2 c corresponds to the 5% Mn doped 2+ Zn3V3O8 nanodisk materials; Figure 2 d corresponds to the 10% Mn-doped 2+ Zn3V3O8 nanodisk materials.

[0103] from Figure 2It can be seen from the analysis that the Zn3V3O8 nanodisk materials prepared in Example 1, Example 2, Example 3 and Control Example 1 all have a typical nanoplate staggered stacking morphology, these nanoplates are formed by the aggregation of nanoparticles, and their morphology does not change significantly before and after doping, the formed nanoplates are evenly distributed, and the larger specific surface area can provide more active sites for full contact with the electrolyte, so that the assembled battery device can have better electrochemical performance.

[0104] 3) Transmission electron microscopy analysis The 5% Mn-doped 2+ The Zn3V3O8 nanodisk material was analyzed by transmission electron microscopy. Figure 3 shown.

[0105] Figure 3 a~ Figure 3 c corresponds to the 5% Mn-doped 2+ TEM image of Zn3V3O8 nanodisk material, Figure 3 d is the corresponding element mapping diagram.

[0106] from Figure 3 From the analysis, it can be seen that Zn, V, O and Mn elements are evenly distributed in 5-ZnVO, which indicates that Mn 2+ Successful doping.

[0107] 4) Cyclic voltammetry test The cyclic voltammetry (scan rate was 0.1 mV s –1 ) The zinc ion button cells prepared in Example 2 and Comparative Example 1 were tested, and the results were as follows Figure 4 shown.

[0108] in, Figure 4 a is the CV curve of the zinc ion button cell prepared in Control Example 1; Figure 4 b is the CV curve of the zinc ion button battery prepared in Example 2.

[0109] from Figure 4 a and Figure 4 As shown in the analysis in b, the CV curves of the zinc ion button cell prepared in Example 2 and the comparative example 1 have good overlap, which proves that the zinc ion button cell doped with 5% Mn prepared in Example 2 2+ The Zn3V3O8 nanodisk material prepared in Example 1 and the undoped Zn3V3O8 nanodisk material prepared in Example 1 have good stability. Figure 4 It can be seen that the CV area of ​​the zinc ion button battery prepared in Example 2 is significantly larger than that of the zinc ion button battery prepared in Control Example 1, thereby proving that the zinc ion button battery prepared in Example 2 has a higher specific capacity.

[0110] Figure 4 c is the GCD curve (constant current charge and discharge curve) of the zinc ion button battery prepared in Example 2, Figure 4 d is the GCD curve (constant current charge and discharge curve) of the zinc ion button battery prepared in Control Example 1.

[0111] from Figure 4 From the analysis of c and 4d, we can see that Zn3V3O8 and 5%Mn 2+ Doped Zn3V3O8 undergoes phase transition during the first charge process. 2+ Doped Zn3V3O8 has significantly higher discharge specific capacity.

[0112] 5) Rate performance test The zinc ion button cells prepared in Example 1, Example 2, Example 3 and Comparative Example 1 were subjected to rate performance tests. The test method was as follows: 0.1-5A g was tested on a blue battery test system. -1 Rate performance of zinc-ion batteries at current density.

[0113] The results are as follows Figure 5 shown.

[0114] in, Figure 5 a is the discharge specific capacity and energy density of the zinc ion button cell prepared in Control Example 1; Figure 5 b is the discharge specific capacity and energy density of the zinc ion button battery prepared in Example 1, Figure 5 c is the discharge specific capacity and energy density of the zinc ion button battery prepared in Example 2, Figure 5 d is the discharge specific capacity and energy density of the zinc ion button battery prepared in Example 3.

[0115] from Figure 5 It can be seen from the analysis that at a current density of 0.1A g -1 When the discharge capacity of the zinc ion button cell prepared in Example 1 is 299.4 mAh g –1 The discharge specific capacities of the zinc ion button cells obtained in Example 1, Example 2, and Example 3 were 313.6 mAh g –1 、333.86mAh g –1 and 262.75mAh g –1 . This proves that after Mn 2+ The doped Zn3V3O8 nanodisk material is used as the positive electrode material of zinc battery, and the discharge specific capacity is significantly improved. 2+ When the doping content is 5%, the battery has significantly higher capacity.

[0116] 6) Cycle performance test The sodium ion button cells prepared in Example 1, Example 2, Example 3 and Comparative Example 1 were subjected to cycle performance tests at a current density of 2 A / g. The results are as follows: Figure 6 shown.

[0117] Figure 6 a is the cycle performance test result of the zinc ion button cells prepared in Example 1 and Example 3 at a current density of 2A / g; Figure 6 b is the cycle performance test result of the zinc ion button cells prepared in Control Example 1 and Example 2 at a current density of 2 A / g.

[0118] from Figure 6 It can be seen from the analysis that at a current density of 2A / g, the capacity retention rate of the zinc ion button battery prepared in the control example 1 after 1500 cycles is 60.26%, the capacity retention rate of the zinc ion button battery prepared in the example 1 after 1500 cycles is 86.98%, the capacity retention rate of the zinc ion button battery prepared in the example 2 after 1500 cycles is 87.5%, and the coulomb efficiency is almost 100%; the capacity retention rate of the zinc ion button battery prepared in the example 3 after 1500 cycles is 78.85%. This proves that after 5% Mn 2+ The doped Zn3V3O8 nanodisk material has better cycle stability as the positive electrode material of zinc battery.

[0119] In summary, the positive electrode material of the present invention undergoes electrochemical conversion during the first charge and discharge process to induce a phase change in the material, where Zn3V3O8 is converted into high-valent vanadate Zn3V2O7(OH)22H2O and Zn x V2O 5-y n H2O makes the positive electrode material form more stable vanadium ions, effectively improving the cycle stability of the positive electrode material, thereby making a battery, which can improve the cycle stability of the battery. At the same time, by doping manganese elements in the Zn3V3O8 nanodisk material, the Mn with high electrochemical activity and high conductivity 2+ Can effectively promote Zn 2+ The rapid electron transfer during the embedding / de-embedding process effectively improves the material's specific capacity, allowing zinc-ion batteries using this positive electrode material to simultaneously achieve more excellent electrochemical performance.

[0120] The method for preparing the positive electrode material of the present invention can effectively prepare a Zn3V3O8 nanodisk material doped with manganese by mixing a metavanadate solution, a zinc salt solution and a manganese salt solution, and then performing a solvent thermal reaction and calcination. The solvent thermal reaction ensures the two-dimensional nano morphology of the product, and the subsequent calcination makes the product have good crystallinity, so that the prepared positive electrode material has good electrochemical performance.

[0121] The zinc ion battery of the present invention adopts the positive electrode plate of the present invention as the positive electrode of the zinc ion battery, which can effectively improve the discharge specific capacity, rate performance and cycle stability of the battery, and has promotion and application value in the technical field of zinc ion batteries.

[0122] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present application. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present application. Therefore, all equivalent modifications or changes made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed in the present application shall still be covered by the claims of the present application.

Claims

1. A positive electrode material, characterized in that: Includes Zn3V3O8 nanodisk material doped with manganese.

2. The positive electrode material according to claim 1, characterized in that The Zn3V3O8 nanodisk material is doped with Mn 2 + ; And / or, the Zn3V3O8 nanodisk material is a spinel Zn3V3O8 nanodisk material.

3. The positive electrode material according to claim 1, characterized in that The doping amount of manganese is 0-10%.

4. A method for preparing a positive electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, mixing a metavanadate solution, a zinc salt solution and a manganese salt solution to obtain a mixed solution; S2, subjecting the mixed solution to a solvothermal reaction to obtain a precursor product; S3. calcining the precursor product to obtain a Zn3V3O8 nanodisk material doped with manganese.

5. The method for preparing the positive electrode material according to claim 4, characterized in that: In S2, the temperature of the solvent thermal reaction is 180°C to 200°C; And / or, in S2, the solvent thermal reaction time is 21 to 24 hours; And / or, in S3, the calcination temperature is 580°C to 620°C; And / or, in S3, the calcination time is 5 to 7 hours; And / or, in S3, calcination is carried out in an inert atmosphere, and the temperature increase method of calcination is programmed temperature increase, and the rate of the programmed temperature increase is 8-12° C. / min.

6. The method for preparing the positive electrode material according to claim 4, characterized in that: The metavanadate is selected from one or both of sodium metavanadate and sodium metavanadate dihydrate; And / or, the zinc salt is selected from one or both of zinc acetate and zinc acetate dihydrate; And / or, the manganese salt is selected from one or both of manganese acetate and manganese acetate tetrahydrate; And / or, the metavanadate solution is obtained by dissolving metavanadate in an organic solvent; And / or, the zinc salt solution is obtained by dissolving a zinc salt in water; And / or, the manganese salt solution is obtained by dissolving a manganese salt in water; Preferably, the organic solvent is selected from ethylene glycol.

7. An application of a positive electrode material obtained by the preparation method according to any one of claims 4 to 6, characterized in that: The positive electrode material serves as an electrode active material of a battery.

8. A positive electrode sheet, characterized in that: The positive electrode active material in the positive electrode plate is selected from the positive electrode material prepared by the preparation method according to any one of claims 4 to 6.

9. A zinc ion battery, characterized in that: The positive electrode sheet as claimed in claim 8 is used as the positive electrode of the zinc ion battery.

10. A vehicle, characterized in that: The vehicle is equipped with the zinc ion battery as claimed in claim 9.